The future of recruitment : using the new science of talent analytics to get your hiring right - Leutner, Franziska; Akhtar, Reece; Chamorro-Premuzic, Tomas (The future of work, 2022)
Recruitment is where organizations are shaped and careers are made, leaving a profound impact on organizations, individual careers, and society as a whole. The Future of Recruitment helps professionals, researchers, employers, and everybody interested in the world of work to understand the past, present, and future of recruitment. Franziska Leutner, Reece Akhtar and Tomas Chamorro-Premuzic describe the modern technologies and ideas that are changing recruitment, many driven by artificial intelligence. They explore new developments like automated video interviews and game-based assessments to select top talent and describe the science that underlies them. Evaluating ethical issues and highlighting how technology might be used to make recruitment and progression at work meritocratic, The Future of Recruitment reflects on longstanding issues in recruitment and its role in building today's unequal world of work. Explaining how we might use technology ethically to tackle past issues and future developments, the study helps define new directions and values for a future of recruitment that serves society, employers, and job seekers alike.